Pretraining Data Quality and Its Impact on Language Model Reasoning Performance - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 14 peer-reviewed papers addressing the following research question: How does pretraining data quality affect language model reasoning benchmark performance v9. 12 claims were extracted from source literature; 1 was independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.7/10. This report is a machine-generated literature synthesis and does not constitute original research.
Machine-generated literature synthesis.